EFFECTS OF A NORDIC WALKING INTERVENTION ON WALKING IN NORMAL ADULTS - Kazumasa Nakagawa; Shin Okazaki (Scientific Publishing House. NSA Press, 2023)
The purpose of this study was to compare and examine gait parameters, hip joint angle, and lower extremity muscle activity during normal walking before and after Nordic walking (NW) intervention. Nineteen healthy male participants (age 26.3 ± 2.4 years) were included in the study. During walking, we measured gait parameters using the footprint-measuring gait analysis system. Аngular changes of the hip joint were measured with an IMU-type portable three-dimensional motion analyzer and the EMG activity of each muscle. The measurements above were performed before and after a one-hour NW training course. The hip joint angle, muscle activity, and gait parameters were compared before and after the intervention with the same participants. In gait parameters, the stride length and walking speed were significantly greater after the intervention, while the cadence decreased significantly. Both hip flexion and extension angles were significantly greater after the intervention. In terms of muscle activity, the rectus abdominis, the tibialis anterior, and the gastrocnemius were very different after the intervention. According to previous reports, employing a large stride length during NW would affect the normal gait after the training. The use of the Nordic pole may have stimulated a substantial forward movement in the lower extremities using the large range of motion of the hip joints. The benefits of NW include enhanced forward propulsion during gait and additional stability during the stance phase due to the greater support surface provided by the poles.